Tumor venéreo transmissível canino com resistência quimioterápica e metástase esplênica. Relato de caso - A. P. Duzanski; A. D. Ortiz; H. B. Fêo; M. W. Fonseca; M. M. Flórez; L. T Rodrigues; F. Michelon; N. S. Rocha (Revista de la Facultad de Medicina Veterinaria y de Zootecnia)
The canine transmissible venereal tumor is a type of round cell cancer that have the particularity of implanting in mucous tissue, when they lose their integrity, at which point the tumour proliferates and may even develop metastases. The tumor typically responds well to vincristine sulfate chemotherapy, although there are cases of resistance to the drug correlated with the tumoral phenotype. We describe herein a genital mixed TVTC case with metastases at spleen and failure at vincristine sulfate chemotherapeutic treatment in a five years old Australian Cattle Dog female. After the cytological, histological and cytogenetic diagnostic, the primary tumor was still characterized in progression phase and showed low major histocompatibility complex expression MHC (4,4 ± 2% class I e 11 ± 4,1% class II. The dog underwent therapeutic splenectomy and ovariohysterectomy and did not present tumor recurrence within 12 months of clinical follow-up.